Keanekaragaman dan Sebaran Tumbuhan Paku (Pteridophyta) di Desa Siraun, Kecamatan Kalumpang, Kabupaten Mamuju - Meliasa, Meliasa; Wahid, Masyitha; Sari, Arlinda Puspita; Tahar, Musrifah; Muis, Nurmuliayanti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to identify the types of ferns present in Siraun Village, calculate the diversity indices, and identify environmental parameters that influence the presence and distribution of ferns at the study site. The research employed a quantitative descriptive method using purposive sampling with transects. The study location was divided into four stations based on the topographic conditions of each station. The results showed that (1) A total of 34 fern species belonging to 16 families were found, including Thelypteridaceae, Blechnaceae, Athyriceae, Dennstaedtiaceae, Gleicheniaceae, Pteridaceae, Lindsaeceae, Marattiaceae, Tectariaceae, Cytheaceae, Polypodiaceae, Aspleniaceae, Lecytidaceae, Lyogodiaceae, Selaginellaceae, and Lycopodiaceae. (2) The Shannon-Weiner diversity index (H’) was 2.583, indicating moderate fern diversity in Siraun Village. The dominance index (C) was 0.109, showing that no fern species dominated the area. The species richness index (R1) was 3.388, categorized as moderate richness. The evenness index (E) was 0.132, indicating low evenness among fern species. The similarity index (IS) was above 50%, indicating a high level of species similarity in Siraun Village. (3) Environmental parameters measured included soil moisture (14.5–41.5%), soil pH (3.3–6.4), air temperature (25.7–36.1°C), and light intensity (2,826.5–7,421 lux). Overall, these values were within the tolerance range for ferns and are suspected to influence the growth and distribution of ferns in Siraun Village.